UL40-mediated NK evasion during productive infection with human cytomegalovirus - Wang, Eddie C. Y. (The National Academy of Sciences, 2002)
Human cytomegalovirus (HCMV) exploits a range of strategies to evade and modulate the immune response. Its capacity to down-regulate MHC I expression was anticipated to render infected cells vulnerable to natural killer (NK) attack. Kinetic analysis revealed that during productive infection, HCMV strain AD169 first enhanced and then inhibited lysis of primary skin fibroblasts by a CD94/NKG2A(+)NKG2D(+)ILT2(+) NK line. The inhibition of cytotoxicity against strain AD169-infected fibroblasts was abolished by prior treatment of targets or effectors with anti-MHC I and anti-CD94 monoclonal antibodies, respectively, implying a CD94/HLA-E-dependent mechanism. An HCMV strain AD169, UL40 deletion mutant could not inhibit CD94/NKG2A(+) NK killing against skin fibroblasts. The contribution of UL40 to evasion of primary NK cells then was tested in a system where targets and effectors were MHC-matched. Primary NK cells activated with IFNα as well as cultured primary NK cell lines showed increased killing against ΔUL40-infected fibroblasts compared with AD169-infected targets. This effect was abrogated by depletion of CD94(+) cells. These findings demonstrate that HCMV encodes a mechanism of evasion specifically targeted against a proportion of CD94(+) NK cells and show that this system functions during a productive infection.